Le Mouvement syndical international. Revue de la Fédération syndicale internationale (F.S.I.)
German ed.: Die Internationale Gewerkschaftsbewegung. Offizielles Organ... (ZO 16028). - Engl.ed.: The International trade union movement. Official organ... (ZO 16031).